SPECIFIC FEATURES OF TECHNOLOGY OF MANUFACTURING A ZINC-COATED TUB WIRE FOR MUZZLE (BOTTLE’ HOOD WIRE) - D. B. Zuev (Литьë и металлургия)
The paper presents the main technical specifications of galvanized low carbon wire for muzzles (bottle’hood wire), consistent with the exploitation requirements to the wire in the manufacture and use of muzzles. The main criteria when selecting the steel grade and upon selection of the technological processes are given.